DIGITAL BRAND AMBASSADOR: PELATIHAN CREATIVE STORYTELLING BAGI PELAJAR UNTUK PROMOSI DIGITAL DESA WISATA BANTARAGUNG, MAJALENGKA, JAWA BARAT - Diana Fajarwati; Barika Barika; Triana Refelina; Dian Ikha Pramayanti; Menik Indrati (JURNAL ABDIMAS PLJ, 2026)
This Community Service Program (PKM) is entitled “Digital Brand Ambassador: Creative Storytelling Training for Students to Promote Bantaragung Tourism Village Digitally, Majalengka, West Java.” This program was initiated due to the fact that the digital promotion of Bantaragung Tourism Village has not yet been optimized, despite its considerable natural and cultural tourism potential. On the other hand, students as the younger generation are closely connected to digital technology and social media, yet they have not been adequately equipped with skills in creating creative storytelling-based content. The purpose of this program is to enhance students’ abilities in producing creative digital promotional content, develop their understanding of creative storytelling techniques, and prepare them to become digital brand ambassadors for the tourism village. The implementation methods include socialization activities, training sessions, hands-on practice in creating digital content (photos, videos, and storytelling captions), as well as assistance in publishing content on social media platforms. This program was carried out participatively using the Participatory Action Research (PAR) approach involving junior high school students and their equivalents in Bantaragung Village. The expected outcomes of this activity include improved digital skills among students in creating engaging promotional content, the establishment of student groups as digital promotion agents for the village, and increased exposure of Bantaragung Tourism Village on social media. Furthermore, this program is expected to create a sustainable impact on the development of tourism village branding through youth participation. Thus, this Community Service Program represents a strategic effort to integrate digital technology, student creativity, and the local potential of the tourism village in supporting community-based economic and tourism development.